"Is the focus in professional rugby ever really on health?": A qualitative study on the uptake of illness prevention guidelines in rugby. (January 2023) - Chesson, Lucy; Jones, Ben; Backhouse, Susan H.
Abstract: Illness prevention is essential for athlete health management, but little is known about its uptake in sport. Prior to the pandemic, the International Olympic Committee (IOC) published a consensus statement recommending illness prevention guidelines are implemented in sports. Yet, little is known about guideline uptake. Therefore, this study aimed to explore the (1) illness experiences of rugby players and athlete support personnel and (2) barriers and enablers to illness prevention guideline uptake in rugby, using the lens of behaviour change theory. In a bid to inform and enhance athlete welfare, we sought to amplify the voices of participants through qualitative inquiry. Between August 2020 and May 2021, 16 semi-structured interviews were undertaken with players and athlete support personnel working across rugby. Analysis was conducted using Braun and Clarke's reflexive thematic analysis. Prior to COVID-19, participants deemed illness to be of little concern, with experience of illnesses and the global pandemic critical enablers to guideline uptake. The rugby environment was a barrier to illness prevention, particularly in women's and academy teams where resource deficiency was highlighted. 'Rugby identity' acted as both a barrier and enabler with participants' passion for rugby driving both guideline adherence and non-adherence. Tackling resource inequalities between men's and women's cohorts is critical to effectively implement guidelines. Coach and player education is essential, and emphasis must be placed on continuing preventative behaviours adopted due to COVID-19. Our findings offer new insight into illness prevention, moving away from prevailing quantitative research, and instead voicing players' experiences. Highlights: Lived experience of illness in sport is rarely considered in the literature. Rugby players' health and performance may be compromised by illness episodes. Experiencing illness influences motivation and actions to uptake illness prevention. Dual careers, lack of funding and limited personnel impacts illness prevention.